2018
DOI: 10.1111/jfbc.12525
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerols of the seed oil ofLinum grandiflorumDesf.: Their composition, cytotoxicity, and hepatoprotective activity

Abstract: The seed oil of Linum grandiflorum was used for centuries as food additive and medicine due to its high content of omega-3. The presented study aimed to characterize the triacylglycerols (TAGs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(78 reference statements)
2
0
0
Order By: Relevance
“…Histopathological examinations of intoxicated liver also supported the biochemical results, by CCl 4 -exposed mice for 48 h showed vacuolar degeneration and micro-fatty changes. These results were in agreement with [45,46], who reported that after CCl 4 treatment, significant liver damage was observed with classic histology of cirrhosis, coagulated necrosis, massive fibrosis, fatty degeneration and formation of regenerative nodules, the treatment of methanolic extracts of Juniperus phoenicea and Cupressus sempervirens for 30 successive days showed amelioration effect on CCl 4 induced hepatotoxicity, decreased steatosis, reduction in central vein dilation and normalization of hepatocytes [46].…”
Section: Discussionsupporting
confidence: 90%
“…Histopathological examinations of intoxicated liver also supported the biochemical results, by CCl 4 -exposed mice for 48 h showed vacuolar degeneration and micro-fatty changes. These results were in agreement with [45,46], who reported that after CCl 4 treatment, significant liver damage was observed with classic histology of cirrhosis, coagulated necrosis, massive fibrosis, fatty degeneration and formation of regenerative nodules, the treatment of methanolic extracts of Juniperus phoenicea and Cupressus sempervirens for 30 successive days showed amelioration effect on CCl 4 induced hepatotoxicity, decreased steatosis, reduction in central vein dilation and normalization of hepatocytes [46].…”
Section: Discussionsupporting
confidence: 90%
“…Liver functions enzymes in serum: Total protein content, albumin level, ALT and AST and ALP as reported previously by Mohammed et al (2018), (GGT) (Hyder et al, 2013). Antioxidant parameters: Lipid peroxide, glutathione concentration (GSH) and catalase as reported by Sadek et al (2016) previously.…”
Section: Parameters Measuredsupporting
confidence: 61%